Sand chronicles. Vol. 03 - Ashihara, Hinako (Viz Media, 2008)
"Sweet 16-year-old Ann returns to rural Shimane from Tokyo for the summer, eager to reconnect with her boyfriend Daigo. But will the allure of their close friends--wealthy brother and sister Fuji and Shika--sunder the romantic ties that have bound Ann and Daigo since they were 12?"-- from title cover.